Inflammatory biomarker concentrations in dogs with gastric dilatation volvulus with and without 24-h intravenous lidocaine - Brunner, Anna; Lehmann, Anna; Hettlich, Bianca; Peters, Laureen M.; Doras, Camille Julie; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2024)
Background: Canine gastric dilatation volvulus (GDV) is characterized by tissue ischemia, reperfusion, and systemic inflammation. Evidence exists that lidocaine exerts anti-inflammatory properties and potentially improves outcome. Design and setting: Prospective, randomized observational cohort study in client-owned dogs with GDV. Objective: The primary objective of the study was the determination of pro- and anti-inflammatory biomarker concentrations in dogs with GDV with and without intravenous (IV) lidocaine therapy. The second objective was the evaluation of side effects of lidocaine. Methods: Of 35 dogs included in the study, 20 dogs were assigned to receive lidocaine (LIDO) (2 mg/kg initially, followed by a continuous infusion at a rate of 50 μg/kg/min over 24 hours) and 15 dogs not to receive lidocaine (NO-LIDO). Plasma concentrations of cytokines (interleukin (IL)-6, IL-7, IL-8, IL-10, IL-15, IL-18, interferon gamma, keratinocyte chemotactic-like, monocyte chemotactic protein, and C-reactive protein (CRP) were measured at admission (prior any therapeutic intervention, T0), immediately after surgery (T1), at 24 hours (T24), and at 48 hours (T48) post-surgery. Results: No significant differences in concentrations of any cytokines were found between the LIDO- and the NO-LIDO group. Significant lower CRP concentrations (median [range]) were found in dogs with lidocaine compared to dogs without at T24 (97.5 pg/mL [46.3-161.7] vs. 127.9 pg/mL [26.9-182.0]; P=0.046) and T48 (73.7 [18.4-169.4] vs. 116.3 [71.4-176.8]; P=0.002). Dogs receiving lidocaine exhibited significantly impaired mentation, a prolonged period of anorexia, and longer hospitalization compared to dogs without lidocaine. Conclusion: Lidocaine administration had no impact on the plasma levels of cytokines during the 48-hour study period, but significantly lower CRP concentrations were found at T24 and T48. Lidocaine's potential side effects require careful decision making regarding its use.